TA`TSIIRU THARIIQAH AL-IKHTIBAARU (HOMPIMPAH) WA MINHU AL-MAKAAFAAT ‘ALAA QADRAH MAHAARAH AL-KALAM LISHAFI AL-‘AASYARA OTKP 1 FII AL-MADRASAH AT-TSANAWIYYAH BOGOR - Aefa Tsuaebah Islamiyah; Asriani; Fatchiatuzahro (SHAWTUL ARAB, 2023)
The application of the test method and the provision of rewards in the first cycle and the second cycle was considered for students to be more active in learning and understanding of students who are increasing in speed and accuracy, especially with short tests and rewards that students became more motivated to learn. The Arabic language in speech skills and leads to an increase in learning and students' understanding of materials related to the elephant, past and present. In the learning process, using the test method and giving rewards for Arabic materials that were arranged in an appropriate way, in the first episode and the second session there was an impact and increase, which is the first episode with an average of 62.0 in the session The second increased to 71.8. At the same time, the students who complete the learning also show an increase, namely in the first cycle it reaches 78.0% with 32 students completing it, while in the second cycle it increases to 97.6% with 40 students completing it out of the 40 students in the tenth class